Rachanatmak and Kriyatmak Review of Twacha in Ayurveda with Reference to Skin - Upadhyaya, Nilkanth; Yadav, Sarika; Yadav, Chhaju Ram (International Research Journal of Ayurveda & Yoga, 2021)
Ayurveda, the world’s utmost ancient science of life, focuses on preventing disease along with treating it. In Ayurveda, Twacha is described as outermost covering and protective layer of the body. Acharya Charaka describes Twacha is the Mula of Mamsavaha Srotas and Upadhatu of Mamsa Dhatu. Twacha is the Adhishthana of Sparshanendriya. Ayurveda describes six or seven distinct layers of the skin, each with its own structure and function. The layers are designed in such a way that each one supports the layer above it. In Ayurvedic classics, various opinions regarding Twacha Uttapati, Twacha Stara and associated disorders are mentioned The seven layers of Twacha proclaimed by Sushruta, corresponds perfectly with the seven skin layers, accepted by western medicine also. Acharya Charaka describes six layers of Twacha and named first two layers while remaining four layers have been described in the term of disease in particular layer. Twak is a reflector of the total health and well-being of an individual. The incidence and impact of diseases of skin are increasing day by day. Disease conditions of Twak cause physical, mental, social and spiritual disharmonies in a person. Hence the necessity of detailed study and analysis of the concept of the Twacha, its Rachanatmak and Kriyatmak aspect is of utmost importance and immense necessary.